The Importance of Investigative Experimentation in the Training of Natural Science Teachers (Interdisciplinary Studies Journal, 2025)
The objective of this research is to carry out a bibliographical study on the importance of approaching Investigative Experimentation in the Training of Natural Sciences Teachers and discuss the potential of this training. To this end, a theoretical survey was carried out in the electronic databases of the CAPES Periodicals Portal, through access from the Federated Academic Confederation (CAFe), via the Federal University of Rio Grande do Sul, in scientific articles, using the keywords “ Investigative Experimentation” and “Teacher Training”. The research is of a qualitative nature and after reading it was realized that teacher training is discussed in documents that govern Education, but that teachers still find it difficult to work with active methodologies, as their training is based on other themes. When teachers propose to work from an investigative perspective, students are led to develop research to solve a problem, making them the protagonist of the learning process, but this requires investment in teacher training.
Keywords: Teacher Training; Active Methodologies; Science Teaching